35 yr of stratospheric aerosol measurements at Garmisch-Partenkirchen: from Fuego to Eyjafjallajökull, and beyond - Trickl, T.; Giehl, H.; Jäger, H.; Vogelmann, H. (Atmospheric Chemistry and Physics, 2013)
Lidar measurements at Garmisch-Partenkirchen (Germany) have almost continually delivered backscatter coefficients of stratospheric aerosol since 1976. The time series is dominated by signals from the particles injected into or formed in the stratosphere due to major volcanic eruptions, in particular those of El Chichon (Mexico, 1982) and Mt Pinatubo (Philippines, 1991). Here, we focus more on the long-lasting background period since the late 1990s and 2006, in view of processes maintaining a residual lower-stratospheric aerosol layer in absence of major eruptions, as well as the period of moderate volcanic impact afterwards. During the long background period the stratospheric backscatter coefficients reached a level even below that observed in the late 1970s. This suggests that the predicted potential influence of the strongly growing air traffic on the stratospheric aerosol loading is very low. Some correlation may be found with single strong forest-fire events, but the average influence of biomass burning seems to be quite limited. No positive trend in background aerosol can be resolved over a period as long as that observed by lidar at Mauna Loa. We conclude that the increase of our integrated backscatter coefficients starting in 2008 is mostly due to volcanic eruptions with explosivity index 4, penetrating strongly into the stratosphere. Most of them occurred in the mid-latitudes. A key observation for judging the role of eruptions just reaching the tropopause region was that of the plume from the Icelandic volcano Eyjafjallajökull above Garmisch-Partenkirchen (April 2010) due to the proximity of that source. The top altitude of the ash above the volcano was reported just as 9.3 km, but the lidar measurements revealed enhanced stratospheric aerosol up to 14.3 km. Our analysis suggests for two or three of the four measurement days the presence of a stratospheric contribution from Iceland related to quasi-horizontal transport, differing from the strong descent of the layers entering Central Europe at low altitudes. The backscatter coefficients within the first 2 km above the tropopause exceed the stratospheric background by a factor of four to five. In addition, Asian and Saharan dust layers were identified in the free troposphere, Asian dust most likely even in the stratosphere.